1971
DOI: 10.2118/3112-pa
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluoric Acid Reaction with a Porous Sandstone

Abstract: A procedure is developed for predicting changes in the porosity distribution in a sandstone resulting from reaction with hydrofluoric acid. This procedure is based on a theory for slow heterogeneous reactions in a porous solid where the solid matrix is consumed in the reaction Process. Reaction-rate data for use in this theory are obtained from experiments where acid is injected through short cores and effluent concentration measured using a fluoride specific ion electrode. This rate is found to be first order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Eq. 6 is similar to one previously mentioned in the literature, 8 though the approaches are different.…”
Section: Dynamic Sandstone Acidizingsupporting
confidence: 57%
“…Eq. 6 is similar to one previously mentioned in the literature, 8 though the approaches are different.…”
Section: Dynamic Sandstone Acidizingsupporting
confidence: 57%
“…To mitigate formation damage due to the fracturing gel, it has been found that lowering pH value can also remove gel residuals and clean up such damage [32,33]. Meanwhile, using acid can also create new flow paths, dissolve suspended fines, and clean up the plugged pores [34][35][36]; in the field, using acid (i.e., acidizing) has already been successfully applied in sandstone reservoirs to enhance the production [37]. Lowpermeability sandstone with well-developed natural fractures has a complex pore structure, where pores and pore throats have a wide range of diameters.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest reports of this phenomenon appeared almost 15 years ago, 1 and numerous others have followed. [2][3][4][5] These observations have been incorporated into general field guidelines that frequently call for large acid volumes just to overcome the damage caused by initial acid injection. Various theories have attributed this initial damage to fines plugging, precipitation of insoluble fluosilicates, and precipitation of silica.…”
Section: Permeability Increase Caused By Hfmentioning
confidence: 99%
“…Silica precipitation from spent hydrofluoric acid can be very damaging to rock permeability. 3. Sandstone formations containing iron-bearing minerals can be acidized successfully.…”
Section: Introductionmentioning
confidence: 99%